Architectural heritage and identity of Russian cities - Shchenkov, Alexei; Antonova, Natalia (project baikal, 2021)
The role of architectural heritage in the formation of identity of Russian cities is poorly studied. The interaction of the tangible and intangible architectural heritage is hardly covered. The article analyses the results of sociological surveys among the local population of a number of Russian historic cities. Regarding the results of these surveys, the authors reveal the specific types of the residents’ perception of the city’s architectural heritage, as well as the connection between its material and virtual components in the image of the city.